Xenon Reduces Neuronal Hippocampal Damage and Alters the Pattern of Microglial Activation after Experimental Subarachnoid Hemorrhage: A Randomized Controlled Animal Trial - Veldeman, Michael; Coburn, Mark; Rossaint, Rolf; Clusmann, Hans; Nolte, Kay; Kremer, Benedikt; Höllig, Anke (Frontiers in Neurology, 2017)
Objective: The neuroprotective properties of the noble gas xenon have already been demonstrated using a variety of injury models. Here, we examine for the first time xenon´s possible effect in attenuating early brain injury (EBI) and its influence on post-hemorrhagic microglial neuroinflammation in an in vivo rat model of subarachnoid hemorrhage (SAH). Methods: Sprague Dawley rats (n=22) were randomly assigned to receive either Sham surgery (n=9; divided into two groups) or SAH induction via endovascular perforation (n=13, divided into two groups). Of those randomized for SAH, 7 animals were post-operatively ventilated with 50 vol% oxygen/50 vol% xenon for one hour and 6 received 50 vol% oxygen/50 vol% nitrogen (control). The animals were sacrificed 24 hrs after SAH. Of each animal a cerebral coronal section (-3.60 mm from bregma) was selected for assessment of histological damage 24 hrs after SAH. A 5-point neurohistopathological severity score was applied to assess neuronal cell damage in H&E and NeuN stained sections in a total of 4 predefined anatomical regions of interest. Microglial activation was evaluated by a software-assisted cell count of Iba-1 stained slices in 3 cortical regions of interest. Results: A diffuse cellular damage was apparent in all regions of the ipsilateral hippocampus 24 hrs after SAH. Xenon treated animals presented with a milder damage after SAH. This effect was found to be particularly pronounced in the medial regions of the hippocampus, CA3 (p=0.040) and dentate gyrus (DG p=0.040). However, for the CA1 and CA2 regions there were no statistical differences in neuronal damage according to our histological scoring. A cell count of activated microglia was lower in the cortex of xenon treated animals. This difference was especially apparent in the left piriform cortex (p=0.017). Conclusion: In animals treated with 50 vol% xenon (for one hour) after SAH a less pronounced neuronal damage was observed for the ipsilateral hippocampal regions CA3 and DG, when compared to the control group. In xenon threated animals a lower microglial cell count was observed suggesting an immunomodulatory effect generated by xenon. As for now, these results cannot be generalized as only some hippocampal regions are affected.